Designing English writing worksheets incorporating Islamic moderation values at an Islamic senior high school in Palopo - Masruddin Masruddin; Rusdiansyah Rusdiansyah; Anisa Zidni Ananda; Ermawati Ermawati; Ahmed Sardi (Studies in English Language and Education, 2025)
This study aimed to design an English writing worksheet integrating Islamic moderation values for tenth-grade students at an Islamic senior high school in Palopo, Indonesia. The research employed a Research and Development (RD) design, using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The worksheet was developed based on a needs analysis conducted with 22 students, following a Task-Based Language Teaching (TBLT) approach. Data collection methods included interviews and a questionnaire for the need analysis, experts validation questionnaires for worksheet evaluation, and a students perception questionnaire. The findings indicated that the designed English writing worksheet, which incorporates Islamic moderation values, consists of: 1) three units of writing materials, 2) five sub-units: Lets Get Ready, Lets Practice, Grammar Focus, Lets Do More, and Lets Review, 3) various task-based language teaching activities, 4) integration of Islamic moderation values, 5) an engaging layout and media, and 6) supplementary skills, including reading, listening, and speaking. The worksheet was tried out with the participants, and the results showed a mean score of 3.8 in the excellent category based on student perceptions. The students interviews supported these findings. In conclusion, the English writing worksheet enhances writing skills and facilitates the practical application of Islamic moderation values in students daily lives.